The influence of seed layer electroplating time on structural properties, optical energy bandgap, diameter, growth orientation and surface roughness of ZnO nanorods - Saraç, Umut; Baykul, M. Celalettin; Saraç, Umut (Springer, 2021)
In this paper, the influence of the seed layer electroplating time (t(seed layer)) on the structural properties, optical energy bandgap, diameter, growth orientation and surface roughness of zinc oxide (ZnO) nanorods (NRs) electrochemically deposited from an oxygenated aqueous zinc chloride electrolyte solution was studied. Prior to actual electrochemical fabrication of subsequent ZnO NRs, the ZnO seed layers were first electroplated on the indium tin oxide (ITO) covered glass substrates at different t(seed layer) values of 25 s, 50 s and 100 s under a constant current density. The subsequent ZnO NRs were electrochemically deposited on the prepared ZnO seed layers at a constant cathode potential. For comparison, the ZnO NRs was also deposited on the ITO-covered glass substrates without a seed layer (t(seed layer) = 0 s). The surface morphologies of the ZnO NRs were characterized using an atomic force microscopy and a scanning electron microscopy. The results revealed that the shape of the ZnO NRs is affected by the t(seed layer) value and the diameter and surface roughness of the ZnO NRs can be reduced considerably by controlling the t(seed layer). The ZnO sample grown at the t(seed layer) of 50 s consisted of completely hexagonal-shaped NRs with the smallest mean diameter and exhibited the smoothest top surface. X-ray diffraction measurements confirmed the creation of the hexagonal wurtzite crystal structure for all samples. The ZnO NRs fabricated at the t(seed layer) of 50 s displayed the best preferential growth orientation along c-axis. Structural analysis also showed that the samples have nano-sized crystallites ranging from 50 to 56 nm. The ZnO NRs without the seed layer had an energy bandgap of 3.318 eV while the ZnO NRs prepared on the seed layers exhibited an energy bandgap value in the range of 3.370 +/- 0.006 eV, which was inversely proportional to the mean crystallite size of the samples.
Keywords: Thin-Films; Nanostructured Materials; Electrodeposition; Transparent; Arrays